Colonial Trauma in Rasina Novel by Iksaka Banu: Postcolonial Psychology Frantz Fanon - Andi Nur Sailal Armi; Usman; Abidin, Aslan (Universitas Cokroaminoto Palopo, 2026)
Colonialism affects not only territorial control but also the psychological destruction of colonized subjects through unequal power relations that generate systemic trauma. This article analyzes the representation of colonial trauma in Rasina by Iksaka Banu using Frantz Fanon’s postcolonial psychological framework. Employing a qualitative descriptive method with an objective approach, data were collected through text analysis and systematic note-taking. The analysis followed Denzin and Lincoln’s model, including data collection, reduction, presentation, and conclusion drawing. The findings indicate that Rasina portrays the profound psychological collapse of its main character as a result of continuous colonial violence. Trauma manifests in literary representation resembling what Fanon terms reactionary psychosis, reflected in self-alienation, severe depression, acute anxiety, and psychosomatic disorders, particularly the loss of speech caused by systemic dehumanization. Unlike previous studies that predominantly emphasize sociological perspectives, this research demonstrates that colonial structures actively produce psychological damage that undermines individual psychological autonomy. This study contributes to postcolonial literary scholarship by offering a focused analysis of the pathological effects of colonial history in modern Indonesian literature.